The Effect of Renal Function and Hemodialysis Treatment on Plasma Vasopressin and Copeptin Levels - Esmée M. Ettema; Judith Heida; Niek F. Casteleijn; Lianne Boesten; Ralf Westerhuis; Carlo A.J.M. Gaillard; Ron T. Gansevoort; Casper F.M. Franssen; Debbie Zittema (Kidney International Reports, 2017)
Copeptin is increasingly used in epidemiological studies as a substitute for vasopressin. The effect of renal function per se on copeptin and vasopressin concentrations as well as their ratio have, however, not been well described. Methods: Copeptin and vasopressin levels were measured in 127 patients with various stages of chronic kidney disease, including 42 hemodialysis patients and 16 healthy participants in this observational study. Linear (segmental) regression analyses were performed to assess the association between renal function and copeptin, vasopressin and the C/V ratio. In addition, clearance of copeptin and vasopressin by hemodialysis was calculated. Results: Both copeptin and vasopressin levels were higher when renal function was lower, and both showed associations with plasma osmolality. The C/V ratio was stable across renal function in subjects with an eGFR >28 ml/min per 1.73 m2. In contrast, the C/V ratio increased with worsening renal function in patients with eGFR ≤28 ml/min per 1.73 m2. During hemodialysis, the initial decrease in vasopressin levels was greater compared with copeptin and, consequently, the C/V ratio increased. This was, at least in part, explained by a greater dialytic clearance of vasopressin compared with copeptin. Discussion: Our data indicate that copeptin is a reliable substitute for vasopressin in subjects with an eGFR >28 ml/min per 1.73 m2, whereas at an eGFR ≤28 ml/min per 1.73 m2, that is, CKD stages 4 and 5, a correction for renal function is required in epidemiological studies that use copeptin as a marker for vasopressin. Intradialytic copeptin levels do not adequately reflect vasopressin levels because vasopressin clearance by hemodialysis is higher than that of copeptin.